Implementation of a Discrete Dipole Approximation Scattering Database Into Community Radiative Transfer Model. Issue 24 (13th December 2022) - Moradi, Isaac; Stegmann, Patrick; Johnson, Benjamin; Barlakas, Vasileios; Eriksson, Patrick; Geer, Alan; Gelaro, Ronald; Kalluri, Satya; Kleist, Daryl; Liu, Quanhua; Mccarty, Will
Abstract: The Community Radiative Transfer Model (CRTM) is a fast model that requires bulk optical properties of hydrometeors in the form of lookup tables to simulate all‐sky satellite radiances. Current cloud scattering lookup tables of CRTM were generated using the Mie‐Lorenz theory thus assuming spherical shapes for all frozen habits, while actual clouds contain frozen hydrometeors with different shapes. The Discrete Dipole Approximation (DDA) technique is an effective technique for simulating the optical properties of non‐spherical hydrometeors in the microwave region. This paper discusses the implementation and validation of a comprehensive DDA cloud scattering database into CRTM for the microwave frequencies. The original DDA database assumes total random orientation in the calculation of single scattering properties. The mass scattering parameters required by CRTM were then computed from single scattering properties and water content dependent particle size distributions. The new lookup tables eliminate the requirement for providing the effective radius as input to CRTM by using the cloud water content for the mass dimension. A collocated dataset of short‐term forecasts from Integrated Forecast System of the European Center for Medium‐Range Weather Forecasts and satellite microwave data was used for the evaluation of results. The results overall showed that the DDA lookup tables, in comparison with the Mie tables, greatly reduce the differences among simulated and observed values. The Mie lookup tables especially introduce excessive scattering for the channels operating below 90 GHz and low scattering for the channels above 90 GHz. Plain Language Summary: Radiative transfer (RT) models have a wide range of applications in remote sensing, satellite data calibration, instrument design, and weather forecasts. Although, the clear‐sky simulations conducted by the RT models are relatively accurate, the accuracy of these models for simulating all‐sky observations remains limited. One of the main reasons for inaccuracies in all‐sky simulations is known to be the scattering databases used to calculate the optical properties of different cloud hydrometeors. We implemented and evaluated a large scattering database, computed using the Discrete Dipole Approximation (DDA) technique, into the Community Radiative Transfer Model (CRTM). The results showed that the simulations conducted using the DDA database are much more accurate than the corresponding simulations conducted using the Mie scattering lookup tables which assumes spherical particles for all hydrometeors. Key Points: The cloud scattering lookup tables of Community Radiative Transfer Model (CRTM) discussed and documented A new scattering database generated using the Discrete Dipole Approximation (DDA) implemented into CRTM The scattering parameters computed using the DDA technique perform considerably better than Mie coefficients for microwave frequencies